Vietnamese EFL pre-service teachers’ perceptions of the effects of teaching practicum experiences on their professional identity development : - Lý, Thị Minh Trang (Trường Đại học Cần Thơ, 2019)
This study explored Vietnamese English as a foreign language (EFL) pre-service teachers’ perceptions of the effects of teaching practicum experiences on their professional identity development. Particularly, the study aimed to find out the supports and challenges of teaching practicum that affect the development of the professional identity of English teachers of pedagogy. Currently, the training of educational human resources, especially English teachers, plays a huge role in the implementation of the national language project. However, studies on the professional identity of English pre-service teachers still remain scarce in the Vietnamese context. Therefore, this paper reports a descriptive research to explore the perceptions of Vietnamese EFL pre-service teachers on the development of professional identities before and after English teaching practicum at high schools in Mekong Delta. The study employed semi-structured interviews and document analysis to collect data from 10 pre-service teacher participating on teaching practicum at high schools. The findings provide deep insights into the English pre-service teachers’ practicum experiences which provided a perceived enhancement in their own professional identities. The study has an important contribution to research on teachers’ professional identities as well as recommendations for pre-service teachers and stakeholders to improve the effectiveness of teaching practicum in the professional development and professional competencies of pre-service teachers in Vietnam.